Implikasi Hikmat Menurut Paulus Dalam Menentang Pengaruh Ajaran Kaum Sofis Di Korintus - Anggi Maringan Hasiholan; Andreas Budi (Manna Rafflesia, 2021)
Paul, Apostle relates the Good News to the wisdom of God that is understood by humans who give themselves to believe in Jesus. However, the presence of the powerful Sophists with the teaching of worldly wisdom and relying on the power of the word of wisdom (sophia logou), has obscured the true meaning of God's wisdom. This study aims to explore the influence of the Sophists in the life of the Corinthian church which caused Paul to explain the true meaning of wisdom. Knowing the background of the wisdom problem in Corinth will give you a complete picture of the wisdom of God that Paul preached. This study applies historical research methods to find out the origin and influence of the Sophists' teachings. The results show that the sophia logou owned by the Sophists has obscured the meaning of the cross of Christ which is the wisdom of God. The wisdom that Paul means in the letter to the Corinthians is the openness of one's mind to believe in the sacrifice of Jesus on the cross which has implications for congregational unity and survival in the face of problems or struggles.